2011
DOI: 10.4251/wjgo.v3.i6.79
|View full text |Cite
|
Sign up to set email alerts
|

Single-nucleotide polymorphisms of matrix metalloproteinases and their inhibitors in gastrointestinal cancer

Abstract: Matrix metalloproteinases (MMPs) are implicated in cancer development and progression and are associated with prognosis. Single-nucleotide polymorphisms (SNPs) of MMPs, most frequently located in the promoter region of the genes, have been shown to influence cancer susceptibility and/or progression. SNPs of MMP-1, -2, -3, -7, -8, -9, -12, -13 and -21 and of the tissue inhibitor of metalloproteinases (TIMPs) TIMP-1 and TIMP-2 have been studied in digestive tract tumors. The contribution of these polymorphisms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 104 publications
(176 reference statements)
1
20
0
Order By: Relevance
“…Single-nucleotide polymorphisms (SNPs) of MMP-1 seems to increase cancer risk of digestive tract tumors (Langers et al, 2011) and recently a À1607 1G-to-2G MMP-1 polymorphism has been associated with susceptibility to both development and progression of lung cancer (Liu et al, 2011). In breast cancer expression levels of MMP-1 have been found altered, suggesting some role for this collagenase (Köhr-mann et al, 2009).…”
Section: Neoplastic Diseasesmentioning
confidence: 99%
“…Single-nucleotide polymorphisms (SNPs) of MMP-1 seems to increase cancer risk of digestive tract tumors (Langers et al, 2011) and recently a À1607 1G-to-2G MMP-1 polymorphism has been associated with susceptibility to both development and progression of lung cancer (Liu et al, 2011). In breast cancer expression levels of MMP-1 have been found altered, suggesting some role for this collagenase (Köhr-mann et al, 2009).…”
Section: Neoplastic Diseasesmentioning
confidence: 99%
“…Studies were performed to evaluate the association of MMP-2 -1306 C/T polymorphism with colon cancer risk [59] . Langer et al [53,60] reported that presence of CC or CT genotype enhances the survival rate of colon cancer patients. There is also a significant association of MMP-2 -735 C/T polymorphism with esophageal cancer risks [54] .…”
Section: Mmps Polymorphism In Tumor Formationmentioning
confidence: 99%
“…MMP-2 polymorphism was investigated mainly in the promoter region, e.g., MMP-2 -1306 C/T, -735 C/T, -790T/G, -955A/C, and -1575G/A in the context of gastrointestinal cancer risk [53] . Studies reported association of gastrointestinal cancer risk with -1306 C/T and -735 C/T polymorphic site worldwide.…”
Section: Mmps Polymorphism In Tumor Formationmentioning
confidence: 99%
“…MMP7 genetic variation and cancer susceptibility have been studied mainly in two promoter polymorphisms (Ϫ181A3 G and Ϫ153C3 T) that have been found to affect protein expression (10,23). Most of the studies showed positive associations of Ϫ181GG genotype with the risk of cancer development among different populations (13).…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular basis of MMP7 up-regulation in gastric cancer remains unclear. Single base pair substitutions in the MMP promoter may create or abolish the transcription factor-binding site, thereby modifying transcriptional activity (23,24). Two common functional SNPs (Ϫ181A3 G and Ϫ153C/T) located in the MMP7 promoter region known to influence gene expression were studied in several disease conditions, including hypercholesterolemia, idiopathic pulmonary fibrosis, and several cancer types (e.g.…”
mentioning
confidence: 99%